Variations in pollinator density and impacts on large cardamom (Amomum subulatum Roxb.) crop yield in Sikkim Himalaya, India - Kailash S. Gaira; Ranbeer S. Rawal; K.K. Singh (Journal of Asia-Pacific Biodiversity, 2016)
Large cardamom (Amomum subulatum Roxb.), a perennial cash crop, cultivated under an agroforestry system in the eastern Himalaya of India, is well recognized as a pollination-dependent crop. Observations on pollinator abundance in Mamlay watershed of Sikkim Himalaya were collected during the blooming season to evaluate the pollinator abundance across sites and time frames, and impact of pollinator abundance on crop yield from 2010 to 2012. The results revealed that the bumblebees and honeybees are most frequent visitors of large cardamom flowers. The abundance of honeybees, however, varied between sites for the years 2010–2012, while that of bumblebees varied for the years 2011 and 2012. The abundance of honeybees resulted in a variation within time frames for 2010 and 2011, while that of bumblebees varied for 2010 and 2012 (p<0.01). The density of pollinators correlated positively with the number of flowers of the target crop. The impact of pollinator abundance revealed that the increasing bumblebee visitation resulted in a higher yield of the crop (i.e. 17–41 g/plant) and the increasing abundance of all bees (21–41 g/plant) was significant (p<0.03). Therefore, the study concluded that the large cardamom yield is sensitive to pollinator abundance and there is a need for adopting the best pollinator conservation and management practices toward sustaining the yield of large cardamom.